Penerapan Model Direct Instruction Berbantuan Permainan Papa Saya Untuk Meningkatkan Keterampilan Proses Sains Pada Siswa - Riana Sintia; Fina Fakhriyah; Siti Masfuah (Journal Prakarsa Paedagogia, 2018)
This research aims to measure the improvement of students’ science process skill and improvement of teacher’ teaching skills through the grade students at SD 2 Panjunan. The result of this research shown there are significant improvement of science process skill between cycle I 68,74% as a good category and cycle II 80,96% as a good category. The mnagement of Direct Instruction model learning also increased in cycle I 82,00% as a very good category to 92,24% as a very good category in cycle II. It proves that used of Direct Instruction model use papa saya can improve science process skills in fourht grade students theme 7at SD 2 Panjunan.